Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma) - Grismer, L. Lee; Wood, Perry L. Jr.; Zug, George R.; Thura, Myint Kyaw; Grismer, Marta S.; Murdoch, Matthew L.; Quah, Evan S. H.; Lin, Aung (Zootaxa, 2018)
An integrative phylogenetic analysis recovers two new species of the gekkonid genus Hemiphyllodactylus (Bleeker) from the Shan Hills of eastern Myanmar. Hemiphyllodactylus ywanganensis sp. nov. and H. uga sp. nov. are nested within the eastern Myanmar clade of a previous genus-wide phylogenetic analysis and form a more exclusive monophyletic group with H. linnwayensis. These species differ from each other and all other Hemiphyllodactylus in having unique combinations of character states involving postmental and subcaudal scale morphology; maximum SVL; digital formulae; numbers of chin scales, circumnasals, intersupranasals (=postrostrals), labials, longitudinally arranged dorsal and ventral scales, and pore-bearing femoroprecloacal scales; as well as subtle differences in coloration and pattern. The phylogenetic affinities of the eastern Myanmar clade are similar to those of an endemic clade of Cyrtodactylus from the Shan Hills in that both are more closely related to Indochinese taxa east of Myanmar as opposed to other Indo-Burmese species. The discovery of these new species underscores the underappreciated herpetological diversity of limestone ecosystems as well as the remote nature of the rugged uplands of the Shan Hills and emphasizes the need for continued field work in this region.